Job demands as predictors of academician's work engagement - Alzyoud, Adel Ali Yassin; Othman, Siti Zubaidah; Mohd Isa, Mohd Faizal (2014)
The aim of this study is to examine the relationship between job demands, namely academic workload, work pressure and work engagement.Data were gathered through questionnaire from a sample of academicians (n = 532) who worked in four public universities (Mu’tah University, The University of Jordan, The Hashemite University and Yarmouk University) located in the southern, middle and northern region of Jordan.Results indicate that both academic workload and work pressure were significant factor in influencing academicians work engagement.These findings generally supported past findings, which suggested that employees are less likely to engage with their work if they are given higher workload and work pressure.The findings were discussed and implications were also put forward.